CRANIOFACIAL DEFORMITIES TREATED BY AUTOLOGOUS FAT TRANSPLANTATION TECHNIQUE: CROSS-SECTIONAL STUDY - Cristian Drochioi; Agop-Forna Doriana; Otilia Boişteanu; Alexandra Manolache; Victor Vlad Costan (Romanian Journal of Oral Rehabilitation)
Aim of study was to determine the types and distribution of craniofacial deformities treated through autologous fat transplantation. Materials and method. The study group included 36 subjects from OMF Surgery Clinic (Iasi), over the period 2009-2016, with defects of diverse etiology located in the cranial-maxillo-facial territory: traumatic, congenital or postoperative, treated by lipo-structure technique with autologous fat grafting. Results. the distribution of etiology in the study group was categorized in two groups: tumoral formation (83,3%) and post-traumatic sequelae (6 cases, 16,7%). Tumoral formations were further categorized as follows: pleomorphic adenoma of the parotid (19.4%), adenoid cystic carcinoma of the parotid (22.2%), mucoepidermoid carcinoma of the parotid (2.8%), gingival-alveolar carcinoma of the mandible (8.3%), basal cell carcinoma of the masseteric region (8.3%), carcinoma of the retromolar triangle (2.8%), squamous cell carcinoma of the left parotid region (skin) (2.8%), squamous cell carcinoma of the menton region extending to the anterior arch of the mandible (2.8%), pelvi-lingual carcinoma (8.3%), carcinoma of the tongue base (2.8%), large maxillary cyst (2.8%). Post-traumatic sequelae were distributed as follows: retractive scars (11.1%), central-facial fracture (2.8%), right posterior lateral-facial fracture and fracture of the temporal bone extending to the parietal bone (2.8%). Conclusions. Tumoral formations are the dominant cause of craniofacial deformities in the cranio-maxillofacial region, with pleomorphic adenomas and adenoid cystic carcinomas being the most frequent. While post-traumatic sequelae are less common, they remain a significant concern, primarily involving retractive scars and fractures